International Comparisons in Valuing EQ-5D Health States: A Review and Analysis - Norman, Richard; Cronin, P.; Viney, R.; King, M.; Street, D.; Ratcliffe, J. (Wiley-Blackwell Publishing, Inc., 2009)
Objective: To identify the key methodological issues in the construction of population-level EuroQol 5-dimensions (EQ-5D)/time trade-off (TTO) preference elicitation studies.Method: This study involved three components. The first was to identify existing population-level EQ-5D TTO studies. The second was to illustrate and discuss the key areas of divergence between studies, including the international comparison of tariffs. The third was to portray the relative merits of each of the approaches and to compare the results of studies across countries.Results: While most articles report use of the protocol developed in the original UK study, we identified three key areas of divergence in the construction and analysis of surveys. These are the number of health states valued to determine the algorithm for estimating all health states, the approach to valuing states worse than immediate death, and the choice of algorithm. The evidence on international comparisons suggests differences between countries although it is difficult to disentangle differences incultural attitudes with random error and differences as a result of methodological divergence.Conclusions: Differences in methods may obscure true differences in values between countries. Nevertheless, population-specific valuation sets for countries engaging in economic evaluation would better reflect cultural differences and are therefore more likely to accurately represent societal attitudes.